2004
DOI: 10.1097/01.md.0000119761.27564.c9
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Cranial Ischemic Complications in Giant Cell Arteritis

Abstract: Cranial ischemic complications (CICs) are among the presenting manifestations of giant cell arteritis (GCA). Yet patients with GCA may develop CICs at a later stage, despite steroid therapy. In the current report we delineate risk factors for CICs, both at presentation and during follow-up, and review the relevant literature. We reviewed charts of 175 patients with GCA. Follow-up data were available for 166 patients. CICs at presentation or developing within 2 weeks of GCA diagnosis were considered GCA related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
73
2
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(88 citation statements)
references
References 28 publications
(32 reference statements)
8
73
2
4
Order By: Relevance
“…In our series, the proportion of patients who developed permanent visual loss (19.1%) was similar to that reported by Gonzalez-Gay et al (2,12) and by Cid et al (9) (2,3,9,11). Although geographic and ethnic factors may be implicated in the differences in the incidence of GCA at different latitudes, they do not seem to influence the expression of visual manifestations.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In our series, the proportion of patients who developed permanent visual loss (19.1%) was similar to that reported by Gonzalez-Gay et al (2,12) and by Cid et al (9) (2,3,9,11). Although geographic and ethnic factors may be implicated in the differences in the incidence of GCA at different latitudes, they do not seem to influence the expression of visual manifestations.…”
Section: Discussionsupporting
confidence: 90%
“…Subsequently, other studies have reported an association between the presence of systemic manifestations, in particular fever, and a lower incidence of visual manifestations or cranial ischemic complications (3,10 -12). However in most studies, laboratory parameters of inflammation did not differ significantly between those with visual loss and those without it (3,12).…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Acute visual loss, attributable mostly to anterior ischemic optic neuritis, and cerebrovascular accidents (CVAs) are among the leading causes of giant cell arteritis (GCA)-related morbidity (1)(2)(3)(4)(5)(6). Permanent partial or complete loss of vision in one or both eyes occurs in up to 20% of patients with GCA and is often an early manifestation of the disease (2)(3)(4).…”
mentioning
confidence: 99%